Melting and crystallization of in-situ polymerized cyclic butylene terephthalates with and without organoclay: a modulated DSC study (eXPRESS Polymer Letters, 2007)
The polymerization of cyclic butylene terephthalate oligomers (CBT) were studied in presence (in 5 wt.%) and absence of an organoclay (Cloisite® 30B) by modulated DSC (MDSC). The organoclay containing samples were produced by dry and melt blending, respectively. The first heating, causing the polymerization of the CBT catalyzed by an organotin compound, was followed by cooling prior to the second heating. The MDSC scans covered the temperature interval between 0 and 260°C. The aim of this protocol was to study the crystallization and melting behavior of the resulting polybutylene terephthalate (pCBT) and its organoclay modified nanocomposites. It was found that the thermal behaviors of the polymerizing and polymerized CBT (pCBT) were strongly affected by the sample preparation. The organoclay suppressed the crystallization of the pCBT produced during the first heating. However, results from the second heating suggest that more perfect crystallites were formed in the organoclay modified pCBT variants. The organoclay also affected the conversion and mean molecular mass of the resulting pCBT which were slightly lower than those of the plain pCBT polymerized under identical conditions.